Síntesis de resinas epóxicas a partir de aceite epoxidado de palma (2010)
The work described here raises the manufacturing of epoxy resin from epoxidized Palm Oil (AEP), obtained by reaction of the Oil Refining Palma (ARP) with acid peroxiformico in terms of microwave heating. The epoxide obtained is mixed with a convenient way of bisphenol A and polestireno recycling of various products for deshechables well have a mixture that is polymerized by the action of a catalyst peroxide methyl after the addition of cobalt oxide, (Co2O3) as ascelerante. Properties such as mechanical strength, hardness, adhesion and corrosion resistance by the action of acids and bases, were improved with the addition of fibreglass hulls and rice at blends made before being dried.